Younger-onset type 2 diabetes associated with increased long-term cancer risk in Chinese adults: A 30-year follow-up of the Da Qing Diabetes Study - Siyao He; Xin Qian; Jinping Wang; Xiaoxia Shen; Yali An; Bo Zhang; Bo Chen; Hui Li; Xiaoping Chen; Yanyan Chen; Yang Wang; Chenggang Jin; et al. (BJC Reports)
Abstract Background We investigated the association between younger-onset type 2 diabetes, duration of diabetes, and cancer risk based on data from the Da Qing Diabetes Prevention Outcome Study (DQDPOS). Methods The analysis recruited 620 younger-onset (age≤50 years) and 649 older-onset (age>50 years) patients with type 2 diabetes, and 310 younger non-diabetes controls (age≤50 years). Multiple regression analysis was used to test the influence of younger-onset diabetes and duration of diabetes on the long-term risk of cancer. Results The annual incidence of all cancer among the non-diabetes, younger-, and older-onset type 2 diabetes was significantly different (3.7, 5.5, and 4.0/1000 person-years, respectively). The standard Cox analysis revealed that the patients with younger-onset diabetes had a significantly higher risk of cancer than those with older-onset diabetes (hazard ratio [HR]:1.81; 95% confidence interval [CI]:1.20–2.73) and younger non-diabetic controls (HR:2.43; 95% CI:1.34–4.41) after adjustment for diabetes duration and other confounders. Stepwise general linear regression model analysis revealed that a longer diabetes-free time was associated with longer lifetime cancer-free years (partial R2 = 0.36, p < 0.001), in addition to the non-modifiable predictor duration of diabetes. Conclusions Younger-onset type 2 diabetes was significantly associated with an increased risk of cancer beyond the influence of diabetes duration.